Indonesian Lingual Variation Use Among Millennials In The Industrial Revolution Era 4.0 - Ratna Juwitasari Emha; Dede Fatinova (Masyarakat Linguistik Indonesia Universitas Andalas, 2021)
It is a fact that language is dynamic, and nothing can not stop it from changing. This dynamism has implications for the use of various languages among Indonesians. The youth mostly uses it because they are active and massive users of technology and social media. This research aims to describe the form and character of the linguistic variation of slang which is popularly used by the millennial generation. In this study, data is taken from social media, and direct informants then analyzed using a qualitative descriptive method. The results showed that four types of linguistic variation of slang which is popularly used by the millennial generation such phonology (32,29%), morphology (22,92%), syntax (4,17%), and semantics aspect (40, 63%). Based on the results, the millennial generation's most dominant type of semantics aspect with 39 data (40, 63%). It means that millennials preferred using more slang utterances modified in semantic elements. Millennials did not completely change or create many new meanings. They retained the meanings of existing references only in the forms of new terms.